Taxonomic reevaluation of Hoplunnis pacifica Lane & Stewart, 1968 and Hoplunnis sicarius Garman, 1889 (Anguilliformes: Nettastomatidae) through morphological and molecular analysis - Segura, Beder Ramírez; Sanchez, Carlos Luque; Torres, Mervin Guevara; Fricke, Ronald (Zootaxa, 2026)
Since their original descriptions, the eels Hoplunnis sicarius and Hoplunnis pacifica have been reported in the eastern Pacific only at larval and adult stages, respectively. This discrepancy has led to ongoing debate regarding their potential synonymy. To reassess the taxonomic classification of these two species, we conducted morphological and genetic analyses of six adult Hoplunnis specimens collected from the tropical waters off northern Peru. Morphological analyses aligned with the taxonomic descriptions of H. pacifica, while mitochondrial COI gene sequences showed less than 0.32% genetic divergence from sequences attributed to H. sicarius. Furthermore, phylogenetic analyses grouped all specimens within a clade containing H. sicarius, distinct from other species in the genus Hoplunnis and family Nettastomatidae. These findings support the hypothesis that the two names refer to ontogenetic stages of the same species. Therefore, we propose that H. pacifica should be considered a junior synonym of H. sicarius.